Express Method for Isolation of Ready-to-Use 3D Chitin Scaffolds from Aplysina archeri (Aplysineidae: Verongiida) Demosponge - Christine Klinger; Sonia Żółtowska-Aksamitowska; Marcin Wysokowski; Mikhail V. Tsurkan; Roberta Galli; Iaroslav Petrenko; Tomasz Machałowski; Alexander Ereskovsky; Rajko Martinović; Lyubov Muzychka; Oleg B. Smolii; Nicole Bechmann; et al. (Marine Drugs, 2019)
Sponges are a valuable source of natural compounds and biomaterials for many biotechnological applications. Marine sponges belonging to the order Verongiida are known to contain both chitin and biologically active bromotyrosines. Aplysina archeri (Aplysineidae: Verongiida) is well known to contain bromotyrosines with relevant bioactivity against human and animal diseases. The aim of this study was to develop an express method for the production of naturally prefabricated 3D chitin and bromotyrosine-containing extracts simultaneously. This new method is based on microwave irradiation (MWI) together with stepwise treatment using 1% sodium hydroxide, 20% acetic acid, and 30% hydrogen peroxide. This approach, which takes up to 1 h, made it possible to isolate chitin from the tube-like skeleton of A. archeri and to demonstrate the presence of this biopolymer in this sponge for the first time. Additionally, this procedure does not deacetylate chitin to chitosan and enables the recovery of ready-to-use 3D chitin scaffolds without destruction of the unique tube-like fibrous interconnected structure of the isolated biomaterial. Furthermore, these mechanically stressed fibers still have the capacity for saturation with water, methylene blue dye, crude oil, and blood, which is necessary for the application of such renewable 3D chitinous centimeter-sized scaffolds in diverse technological and biomedical fields.